Analisis Pengaruh Net Income, Operating Cash Flow, Dan Debt To Equity Ratio Terhadap Dividend Per Share Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Michelle; Vidyarto Nugroho (Jurnal Ekonomi, 2017)
The purpose of this study is to examine the effect of net income (EAT), operating cash flow (OCF), and debt to equity ratio (DER) towards dividend per share (DPS) on manufacturing companies listed on the Indonesia Stock Exchange in 2012-2015. The sampling method used was purposive sampling. The number of samples that met the criteria was 172 companies. Data were analyzed using multiple linear regression analysis. The results showed that, simultaneously, all variables had a significant effect on DPS. Partially, the variable that had significant effect was EAT, while OCF and DER had no significant effect. Furthermore, the coefficient of determination (R2) showed that the effect of variables EAT, OCF, and DER simultaneously to DPS was 30,3%.